ANALYSIS OF QUALITY OF SERVICE OF THE 4G LTE NETWORK IN THE WATERFRONT AREA OF PONTIANAK CITY - ., Suhardi; Yacoub, Redi Ratiandi; Ade Putra, Leonardus Sandy; W, F. Trias Pontia; Imansyah, Fitri (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Internet availability must be sufficient to meet the needs of the era, supported by extensive coverage and robust network stability. Every provider competes in the current internet market, especially in Pontianak City. This research aims to analyze the Quality of Service (QoS) of the 4G LTE networks provided by three widely-used providers in the community. The research results indicate that the Quality of Service of the 4G LTE network in the Waterfront area of Pontianak City falls into the good category. Measurements in the afternoon show good quality, supported by the close proximity between the research location and the Base Transceiver Station (BTS) without interference. However, data transfer speed experiences a decline in some measurements, especially during cloudy weather and busy visitor periods, affecting network jitter parameters. In the evening measurements, despite obtaining fairly good values on some parameters, throughput still receives a poor rating. The decrease in quality in jitter parameters occurs on the first and second nights due to the density of visitors and excessive queuing in the network. The reasons for the poor quality of the cellular network include obstacles from tall buildings, longer transmission distances due to river expanses, and bad weather. Internet user density also affects signal strength. Furthermore, the distance between the BTS and devices plays a crucial role in network propagation, so an efficiently designed 4G network should provide even coverage and consistent quality.